2018
DOI: 10.3389/fimmu.2018.02949
|View full text |Cite
|
Sign up to set email alerts
|

Human T2R38 Bitter Taste Receptor Expression in Resting and Activated Lymphocytes

Abstract: The human G-protein-coupled bitter taste receptor T2R38 has recently been demonstrated to be expressed on peripheral blood neutrophils, monocytes and lymphocytes. To further define a potential contribution of the T2R38 receptor in adaptive immune response, the objective of this study was to analyze its expression in resting and activated lymphocytes and T cell subpopulations. Freshly isolated PBMC from healthy donors were used for expression analysis by flow cytometry. Quantum™ MESF beads were applied for quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 50 publications
2
60
0
Order By: Relevance
“…Moreover, some required genes for bitter‐sensing, such as α‐gustducin and Trpm5, are also critical to initiate a type 2 immune response 30,31 . Human lymphocytes also directly express TAS2R 32 . These reports are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, some required genes for bitter‐sensing, such as α‐gustducin and Trpm5, are also critical to initiate a type 2 immune response 30,31 . Human lymphocytes also directly express TAS2R 32 . These reports are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the mechanism and the specific TAS2R involved in each process remains to be elucidated, our data suggests that "bitter" molecules present endogenously in the BM microenvironment, such as amino acids (71,72), or extrinsic factors, such as drugs (42,73), might interact with TAS2Rs and affect leukemia cell functions. Since, previous data (74) and our unpublished observations indicated that TAS2R were expressed also in healthy hematopoietic cells, we could speculate that TAS2R may represent a novel receptor-based pathway by which blood cells "taste" their microenvironment and respond to it accordingly.…”
Section: Discussionmentioning
confidence: 79%
“…have been claimed to mediate an anti-inflammatory effect [22,23]. Because of the well-known role of both an efficient immune response and an optimal control of inflammation in the attainment of longevity [24,25], these mechanisms might explain the association of TAS2R with longevity.…”
mentioning
confidence: 99%